Hippocampus and dentate gyrus morphological сhanges in posterity of female rats after receiving PgE2 for labor induction. - E. A. Hrygorieva; I. Y. Mamay (Морфологія, 2019)
Background. The effect of labor stimulation on the brain structure still remains an unexplored issue. Objective. To determine the morphological hippocampus and dentate gyrus changes in laboratory rats on the first day of life after intravaginal injection of prostaglandin E2 for labor induction. Methods. The changes in the structure of hippocampus and dentate gyrus in posterity of white syngenic rats on the first day of life have been studied. Pregnant females of the experimental group were injected PgE2 in the form of a gel intravaginally to stimulate labor on the 22th day of pregnancy. The duration of the experimental rats pregnancy amounted to 23 day, in the intact group - 23-24 day after conceiving. The cerebral hemisphere was fixed in a 10% neutral formalindegid solution, dehydrated in an ascending battery of ethyl spirits. 5 μm paraffin sections were stained with hematoxylin and eosin. The thickness of the layers of hippocampus and dentate gyrus, the number of cells of the granular and pyramidal layers per unit area and their sizes, the area of the neurons nuclei of hippocampus and dentate gyrus were determined in the histological samples. Results. Hippocampus and dentate gyrus in posterity of female rats after receiving PgE2 for labor induction is characterized by a thinning of the pyramidal and granular layers, a decrease in the area of the neurons nuclei, and a decrease in the perimeter of the neurons pericarion neurons in all the studied zones. The decrease in the number of cells is determined only in the dentate gyrus. Conclusion. 1. On the 1st day of life in posterity of female rats after receiving PgE2 for for labor induction there is a tendency to thinning of the pyramidal layer of CA1, CA2 and CA3 fields of hippocampus in combination with a decrease of neurons size of the CA1 field of hippocampus in the experimental group compared to the intact one. 2. In experimental rats there is a decrease of the area of neurons nuclei in the regions CA1, CA2, CA3 and the dentate gyrus compared with the control group. 3. The morphological changes of the hippocampus and dentate gyrus in posterity of female rats after receiving PgE2 for labor induction correspond to the brain changes after experimental fetal hypoxia.